FRESH SALES CONCRETEDESIGN SYSTEMS PTINDO BETONUSING MICROSOFT VISUAL BASIC 6.0 - Nevi Viranta Indria Febrianti; Cut Asiana Germawaty, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Division Sales is a very important part to advance the withdrawal of a company, because of where the goods or services a company will be marketed or sold to generate revenue for the company itself. By using the existing sales process and then sets them into the new system, with the aim that is expected to further enhance the sales process.Explanation can be seen from the DFD which consists of context and diagam Zerro diagrams, ERD and normalization, as well as components such as customer management data, the goods. By limiting the problem there is only credit sales process, then made a simple program that uses Visual Basic 6.0 programming language that writers ask for help processing the data mentioned above.